การเตรียมอนุภาคเงินระดับนาโนในตัวทำละลายอินทรีย์ - อรพร วงษ์อุระ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
Silver nanoparticles (AgNPs) have attended a great interest due to their shape- and sizedependent to optical, electrical and chemical properties. As AgNPs are mostly syntheses in aqueous solution thought the reduction mechanism of silver ions (Ag+) and strong reducing agent, however, some specific applications may call for the transfer of the formed AgNPs from a polar (aqueous solution) to non-polar environment (or vice versa) after synthesis. This study focuses on the development of a simple approach by using cationic surfactant, namely Tetraoctylammonium bromide (TOAB), as capping agent to modify the hydrophilicity / hydrophobicity of the AgNP surface. Phase transfer of the already formed AgNPs from a polor (aqueous solution) to non-polor environments (toluene and chloroform media) have been accomplished at room temperature and neutral pH using the optimal amount of the surfactant (TOAB). Phase transfer of silver nanoplate (AgNPls) using the approach is also investigated. In addition, dispersibility and stability of AgNPs in toluene media was evaluated by mixing with polystyrene. It was found that the transferred AgNPs is highly dispersed and stable in the polystyrene strap as they do not reach from the strap after adding the etching agent (sodium chloride).